Technology-Based Methods and Resources in Contemporary Language Learning - Khamzakulova Shakhnoza Khudayar Kizi (Academia Open, 2026)
General Background: The integration of technology has fundamentally transformed language learning paradigms, particularly within ESL, ESP, and L2 contexts. Specific Background: Since the emergence of PLATO systems in the 1960s, technological evolution has progressively incorporated hardware, software, and internet-based solutions into language pedagogy. Knowledge Gap: Despite substantial technological advancement, critical issues persist regarding pedagogically appropriate application, adequate teacher preparation, and strategic tool selection aligned with specific linguistic competencies and learning objectives. Aims: This study examines the historical trajectory of technology in language learning, categorizes technological tools, and evaluates their pedagogical effectiveness across different language skills. Results: Findings reveal that hardware components (auditory and visual tools) and software categories (CAI, CALL, ICALL, WBLL, MALL) demonstrate distinct contributions to listening, speaking, reading, and vocabulary acquisition, with applications such as Duolingo, Babbel, and Rosetta Stone showing progressive development. Novelty: This research synthesizes historical, theoretical, and practical dimensions to analyze the interaction between technological innovation, linguistic theories, teaching standards, and emerging digital learning ecosystems. Implications: Effective technology integration necessitates evidence-based pedagogical approaches, explicit implementation frameworks, and comprehensive teacher training to ensure that digital tools enhance rather than merely supplement traditional language instruction.Highlight : Technology has transformed language learning from PLATO systems in the 1960s to current mobile applications and virtual platforms. Technological tools divide into hardware (sound and visual tools) and software (CAI, CALL, ICALL, WBLL, MALL) for developing specific linguistic skills. Effective technology integration requires evidence-based pedagogy, systematic implementation, and adequate teacher training to support language instruction. Keywords : Technology in Language Learning, Computer-assisted Language Learning (CALL), Mobile-assisted Language Learning (MALL), Language Learning Applications, Digital Language Pedagogy